Additive manufacturing - Matos, Florinda (2019)
The authors gratefully acknowledge: (a) The funding of Project FIBR3D (ref: POCI-01-0145-FEDER-016414), co-financed by Fundo Europeu de Desenvolvimento Regional (FEDER) and by National Funds through FCT— Fundação para a Ciência e Tecnologia, Portugal; (b) FCT grant (ref: grant UID/EMS/00667/2019); (c) the funding of Project KM3D (PTDC/EME-SIS/32232/2017), supported by Fundação para a Ciência e Tecnologia, Portugal; and (d) the four organizations participating in the case studies.